(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Famous pedagogue, enlightener and trainer, founder of judo Dzigoro Kano (1860-1938) came to Kyoto from Hyogo as a child and studied at Naritatsugaki and Ikuei boarding schools. Since birth, he has been quiet grew up, so he decided to master the methods of jujutsu did Kaisei Lyceum, which later became Tokyo Imperial University after entering Kano Dzigoro Tensinine began to attend the wrestling hall and he there under the guidance of coaches Fukuda Hatinosuke and Iso Masatomi learned the technique and engaged in training. Then it is completely Ikubo Tsunetoshi is a coach at a school of another direction - Kitoryu School studied under the guidance of, elaborated manuscripts on jujutsu analyzed and learned the methods of fighting with his whole body.